“What country, friends, is this?”: Displaced Identity and Homoerotic Desire in Twelfth Night and Its Italian Models - Lawrence, Jason (Routledge, 2024)
This chapter challenges the critical consensus that Barnabe Riche’s prose tale “‘Of Apolonius and Silla”’ (1581) is the “‘most immediate source”’ for Shakespeare’s Twelfth Night (1601) by examining in detail the play’s relationship with two Italian models, neither of which has ever been universally accepted as a direct “‘source”’, despite Geoffrey Bullough’s suggestion in the late 1950s that the English playwright might have been familiar with both: the prose comedy Gl’ Ingannati (1537), written and performed by the Sienese Academy of the Intronati in 1532, and Matteo Bandello’s previously neglected prose story of “Nicuola innamorata di Lattanzio” (II, 36) in the Novelle (1554). The chapter argues that the relationship between Fabrizio and the Pedant from act 3 onwards in the Italian comedy provides a model for the equivalent scenes between Sebastian and Antonio in the English play, and it also demonstrates that Shakespeare engages directly with Bandello’s version of the story in Italian in developing the cross-dressing character of Viola / Cesario from the moving figure of Nicuola / Romulo in the prose tale, particularly for his dramatic denouement in which the long-lost male-female twins are miraculously reunited on stage.
Keywords: Shakespeare’s Twelfth Night; Bandello; Gl’Ingannati; source studies